Soundscape and subjective factors affecting residents’ evaluation of aircraft noise in the communities under flight routes - Qu, Fei; Li, Zhuoming; Zhang, Tongtong; Huang, Wenjun (Frontiers in Psychology, 2023)
Introduction Aircraft noise is one of the most significant sources of environmental pollution in large cities. During the COVID-19 pandemic, strict lockdown in community might increase residents’ discomfort with the noise, which could disrupt public activities and reduce subjective well-being. Most of the existing studies considered aircraft noise as a single sound source, which have ignored the influence of other sounds in the community. This paper applied field survey to identify the soundscape and non-acoustic factors related to aircraft noise evaluation. Methods Paper questionnaires were delivered to select residents of three sample residential areas near Shenzhen Bao’an International Airport to investigate residents’ general health, evaluation of aircraft noise, community activities, and attitudinal factors. The relationship between respondent’s noise evaluations and subjective factors were investigated through statistical analyses controlling for measured aircraft noise levels and the existence of soundscape facilities. Results The results indicated that the negative effects of aircraft noise were enhanced during the lock down, especially for frequent space users and those residents in poor health status. Under conditions of similar levels of aircraft noise exposure, communities with more birdsong and fountain sounds had lower proportion of highly annoyed respondents and higher level of soundscape ratings. This paper further indicated that personal factors including fear of air travel, noise sensitivity, and the frequency of outdoor activity had increased the level of annoyance to aircraft noise, while higher degree of annoyance to aircraft noise was associated with poor health status. Discussion The findings implied the moderating effects of subjective factors and the restorative effects of natural sounds, which could inform aircraft noise control and community consultation strategies by protecting vulnerable populations and creating community soundscape facilities. Future research might conduct a pre- and post-experiment to estimate the potential causal impact of the soundscape intervention.